Panic fiction : women and antebellum economic crisis - Templin, Mary, 1959- (The University Alabama Press, 2014)
"Panic Fiction explores a unique body of antebellum American women's writing that illuminates women's relationships to the marketplace and the links between developing ideologies of domesticity and the formation of an American middle class"--